Insecticidal activity of Acmella paniculata leaf and flower extracts against the fall armyworm, Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae) - Hagus Tarno; Raden Roro Almira Linda Wibowo; Yogo Setiawan; Jianguo Wang; Kunihiko Hata (Cogent Food & Agriculture)
The fall armyworm, Spodoptera frugiperda is a polyphagous crop pest in Indonesia. This study aimed to identify and assess the bioactivity of the insecticide compounds in Acmella paniculata against S. frugiperda. The leaf extract revealed isoamyl acetate (56.45%) and 4-vinylguaiacol (16.64%). The flower extract contained amyl propionate (17.22%), 4-vinylguaiacol (16.64%), and deanol (14.50%). The flower extract has insecticidal activity with the highest mortality rate (72–92%) at a concentration of 13%. The LC50 value of the flower extract is lower (6.236–8.769%) than the leaf extract (11.798–15.443%). Likewise with LC90, where the flower extract (10.945–15.453%) is more effective than the leaf extract (17.222–19.779%). The flower extract also inhibited the growth of S. frugiperda. At 48 hours after treatment (HAT), inhibition reached 83.87%, while at 72 HAT it was 75.33%. Exposed larvae grew smaller, weighing only 7.98 mg at 72 HAT. The highest antifeedant effect was found in flower extract with a concentration of 13%, amounting to 74.87%. Amyl propionate and 4-vinylguaiacol are suspected as active components of the insecticide. With its effectiveness in controlling S. frugiperda, A. paniculata flower extract has the potential as an environmentally friendly biopesticide for controlling corn pests in Indonesia.